Long‐term impacts of grazing management on land degradation in a rural community of Southern Italy: Depopulation matters. (20th April 2020) - Quaranta, Giovanni; Salvia, Rosanna; Salvati, Luca; Paola, Velia De; Coluzzi, Rosa; Imbrenda, Vito; Simoniello, Tiziana
Abstract: Depopulation and economic marginalization of rural districts have induced a progressive land abandonment in agricultural and pastoral districts. In Europe, areas at higher risk of farmland abandonment are characterized by low‐intensity pasture systems whose fate is strongly dependent on state incentives or subsidies to rural development promoting more sustainable land‐use trajectories. Especially in Southern Europe, undergrazing is the main driver of pasture degradation. In such a context, a land management preserving pasture resilience requires a wider knowledge about the impact of practices on the ecological characteristics of pastures and an improved understanding of complex socio‐environmental interactions underlying the adoption of such practices. Based on these premises, this study investigates the extent to which the past land management reflects the current state of agro‐pastoral systems in a local community of Southern Apennine (Basilicata, Italy). Based on a multi‐scale analysis integrating multiple sources of data and exploratory techniques, three land‐use trajectories with different implications for land degradation were identified: (a) areas completely abandoned, (b) areas with a decrease in grazing where the management system is remained unchanged, and (c) areas characterized by a decrease in grazing with changes in the management system. Results outline the importance of landscape history shaping (optimal and sub‐optimal) land management and the influence of landscape structure on livestock performances within different farm management types.